The Influence Of E-Service Quality And Promotion Through PLN Mobile On Customer Satisfaction At PT PLN (Persero) Medan Region - Putri Theresia Dory; Djames Siahaan; Desri Wiana (CERED Indonesia Institute, 2023)
This research aims to analyze the influence of e-service quality and promotion on customer satisfaction both partially and simultaneously. Types of research is quantitative. The population in this research is PT PLN (Persero) Medan Region, Medan City, North Sumatra with population as many as 1031 customers. The types and sources of fata secondary. The sampling technique uses probability sampling technique. The formula in this research uses the Slovin Formula. The results showed that e-service quality partially had a positive and significant effect on customer satisfaction through PLN Mobile at PT PLN (Persero) Medan Region. Promotion has a positive and significant effect on customer satisfaction through PLN Mobile at PT PLN (Persero) Area Medan. E-service quality and promotion simutaneously have a positive and significant effect on customer satisfaction through PLN Mobile at PT PLN (Persero) Area Medan.